2015
DOI: 10.1353/jda.2015.0171
|View full text |Cite
|
Sign up to set email alerts
|

Does organizational culture moderate the relationship between ISO 9000 soft factors and organizational performance?

Abstract: The effective quality management system implemented can lead to improve the performance of organization and also enhance their competitive advantage in the global market. The inconsistent findings from published works on the relationship between ISO 9000 and organizational performance may due to the commitment to implement the ISO 9000 requirements or the culture that is established in the organization. Limited research has been done as well focusing only on the soft factors of ISO 9000 and organizational perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…It is also confirmed by other authors (Saad and Asaad, 2015;Altaf, 2011;Gimenez-Espin, 2013;Neagu and Nicula, 2012), who consider culture as the "personality" of an organization which influences the behavior of employees in various areas, among others: in the management process, innovation, work standards, approach to risk and change, etc. Culture, therefore, manifests itself in almost every area of an organization.…”
Section: Culture Of Enterprises 1168supporting
confidence: 61%
“…It is also confirmed by other authors (Saad and Asaad, 2015;Altaf, 2011;Gimenez-Espin, 2013;Neagu and Nicula, 2012), who consider culture as the "personality" of an organization which influences the behavior of employees in various areas, among others: in the management process, innovation, work standards, approach to risk and change, etc. Culture, therefore, manifests itself in almost every area of an organization.…”
Section: Culture Of Enterprises 1168supporting
confidence: 61%
“…Soltero and Waldrip [78] also indicated that a culture of continuous improvement in a firm can facilitate the adoption of environmental management practices and principles. Some practitioners and specialists believe that the degree to which the cultural values are shared determines the impact of a company's capabilities and resources on its performance [79,80].…”
Section: Lean Culturementioning
confidence: 99%
“…Some special cultures within organizations could possibly result in more efficient financial performance (Ogbonna and Harris, 2000). Some practitioners and specialists believe that the degree to which the cultural values are shared determines the impact of a company’s capabilities and resources on its financial performance (Ali et al , 2016; Saad and Asaad, 2015). Despite its importance, no research exists concerning how halal culture (as a type of organizational culture) moderates the impacts of HOS (as resources of halal firms) on halal firms’ financial performance.…”
Section: Introductionmentioning
confidence: 99%